2008
DOI: 10.1097/brs.0b013e31816c8b4e
|View full text |Cite
|
Sign up to set email alerts
|

Dual Growing Rod Technique Followed for Three to Eleven Years Until Final Fusion

Abstract: Dual growing rod technique resulted in 5.7 +/- 2.9 cm of spinal growth during a 4.37 +/- 2.4 year treatment period. There was significantly greater growth and correction achieved in those lengthened more frequently.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
182
4
10

Year Published

2012
2012
2022
2022

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 329 publications
(204 citation statements)
references
References 10 publications
8
182
4
10
Order By: Relevance
“…The authors concluded that the dual growing rod technique was safe and effective, and had an acceptable rate of complications compared with previous reports while preserving near-normal growth [10]. Consistently better results have been reported with the use of double rods instead of a single one [11,12].…”
Section: Conception and Historysupporting
confidence: 51%
See 4 more Smart Citations
“…The authors concluded that the dual growing rod technique was safe and effective, and had an acceptable rate of complications compared with previous reports while preserving near-normal growth [10]. Consistently better results have been reported with the use of double rods instead of a single one [11,12].…”
Section: Conception and Historysupporting
confidence: 51%
“…While this determination is an important milestone in the treatment of early-onset scoliosis, it also brings with it the question of whether growth is preserved or stimulated. Patients in Akbarnia et al's [10,12] series who were, for various reasons, lengthened more frequently than 6 months showed a greater amount of growth. Yilmaz et al [40] showed in their experimental study on 12 immature pigs that vertebral growth continues during growing rod treatment at an accelerated but statistically not significant rate.…”
Section: S128mentioning
confidence: 93%
See 3 more Smart Citations